تطوير الألعاب اللغوية لتعليم المفردات باستخدام برنامج "سمارت أب جريتور" على أساس نظام الأندرويد بمدرسة نور الحكم الثانوية الإسلامية ستوبندو: Development of Language Games for Teaching Vocabulary Using the Smart App Creator Program on Android at Nurul Hikam Islamic Senior High School Situbondo - Ana Nurjannah; Bambang Irawan; Maskud Maskud; Moh. Yusuf Hidayat (Journal of Arabic Language Teaching, 2024)
The researcher has noticed about the Arabic Language education process at Nurul Hikam Islamic Senior High School in Situbondo it is known that students' enthusiasm for interest in learning vocabulary is still weak. The researcher believed that the teaching of the Arabic language in the Islamic Secondary School in Situbondo city needs an innovative educational method, especially in teaching Arabic language vocabulary, because teaching vocabulary is the basis of language education. The researcher will use the Smart App Creator program in the manufacture of educational aids (language games). The researcher presented three questions: 1) to develop language games to teach vocabulary based on Android 2) to know the feasibility of developing language games for teaching vocabulary based on Android 3) to know effective is the use of language games to teach vocabulary based on Android. The researcher uses ADDIE research. The data was collected through observation, interview and questionnaire. The data sources are from the head of the school and the teacherThe research uses pre-test and pos-test with analysis of this research is quantitative analysis using SPSS 22.0.